Da petição inicial à contestação: o papel da argumentação nas peças processuais - Silva, Marcos Aurélio Gomes Alves da (2013)
The conflict of interests among people is a natural phenomenon, since they were willing to live in society. Man's life is permeated by conflicts, by their very nature to defend their interests. Society went through a period in which the interests were solved in a particular way, with the use of moral, economic or physical force, such as the law of retaliation (an eye for an eye, a tooth for a tooth). In order to solve this type of conflict, the State arises, acting as an instrument of social peace, through the judiciary, represented by the Judge. The establishment of rules of life in society aims to end the violence generated by the discussions, or at least diminish it. Access to this jurisdictional provision is by means of a lawsuit. However, not all conflicts are of interest to the judiciary, which will analyze only those cases where there is a claim resisted, i.e., there must be a resistance of a part to grant the claim of another. This dissertation aims at analyzing the request and its respective initial defense of a divorce action of direct litigation, which portrays a conflict of interest between individuals. Procedural documents chosen for analysis are the foundations for a sentence, and because of its relevance, the argumentative techniques employed by the parties, through their lawyers, in order to persuade and obtain the support of the judge will be observed. For the analysis we used the linguistic theory of argumentation and rhetoric, through which we seek to verify the argumentation techniques and how they were used in the application and in its defense. So, the concepts and universal and particular audiences, the development process of argumentation, particularly its beginning, the nature of the arguments, their presence features, emotions and hierarchy of values were reported in the analysis. The results show that both the initial petition as contestation are steeped in arguments that enhance the parties' arguments, hierarchize values and seek to influence the moods and passions of the judge. The objective of this work was to show the contribution of Linguistics, through the theory of argumentation and rhetoric, for the better understanding of the pleadings in the study, looking forward to identifying the argumentative strategies present in them. Keywords: argumentation; rhetoric; linguistic; Law; pleadings.